Análisis multitemporal de la expansión urbana de los municipios de Fonseca y Barrancas del departamento de La Guajira, Colombia (2022)
The present work shows a multi-temporal analysis, identifying the growth of the urban areas of the municipalities of Fonseca and Barrancas in the department of La Guajira, Colombia, through the analysis of possible factors and/or scenarios of transformation and development in the study area. The foregoing, through the use of satellite images from different periods, processed with analysis tools of Geographic Information Systems (GIS). The analysis of these changes will serve as a tool for future decision making, due to the accelerated urban growth that occurs in La Guajira, for which it is sought that this expansion be carried out in a more organized manner. To perform the analysis, Landsat satellite images from the years 1985, 2000, 2014 and 2021 are used with a supervised classification with the ERDAS Imagine software. According to the digital processing of satellite images, the urban area of Barrancas and Fonseca was identified for the different periods evaluated, where there was evidence of an increase in the area of the municipal capital and its directly proportional relationship with the population of the municipalities, where the The highest annual growth rate of the urban area was between 1985 and 2000. Similarly, the influence on the change in coverage from the presence of the mining industry near the municipalities stands out.